TRAINING CONTRACTOR PERSONNEL IN TERMINATION PRINCIPLES AND PROCEDURES. - Smith, Edward Paul (The Accounting Review, 1945)
The members of the American Accounting Association have an unusual opportunity for rendering an extremely valuable service to our country, one which, if handled properly, cannot ever be measured in dollars, but which will, from an economic standpoint, contribute materially to the well-being of the United States in the period through which we are now passing and the one which will follow immediately upon the cessation of hostilities. The author has had the opportunity, for the past several years, of practically living and breathing government procurement and contracting. He has spent many days, evenings and nights with representatives of both the War and the Navy Departments in endeavors to aid in the solution of the multitude of contract problems that arise in procurement for war purposes. The major problem of our country today, is, of course, the winning of the war. The second major problem of our country today is the winning of the peace. Closely connected with each and part of both is the transfer of our economic structure from a war basis to a peace basis.